PI and Fuzzy Logic Control of Photovoltaic Panel Powered Synchronous Boost Converter - Yüksel, Ahmet; Cora, Adnan (Fırat University, 2017)
In this paper, control of DC/DC synchronous boost converter for photovoltaic panels with different controllers is simulated in the Matlab/SIMULINK software. Firstly, synchronous boost converter is simulated, and then regarding to the changes in reference and source voltages traditional PI and Fuzzy Logic control is achieved. Results obtained are analyzed and compared.